A Case study examination of managerial activities in four UK trade unions formed by merger - Dempsey, Michael (Cranfield University, 2004)
In 1985, the researcher took up employment in what he regarded as a senior management position as Assistant General Secretary (Administration) of NALGO, the public service union. The objective was to gain management experience alongside continuing management education. Whilst there were others seeking to manage to the best of their ability, the idea was not universally accepted. However, the union, by the end of the decade, had embarked on management development courses for senior managers and by the time it merged and became part of UNISON, managerial activities were visible in many areas. It was not, however, clear the extent to which – if at all – such phenomena were observable in other trade unions. The literature did not help in this respect. Research to establish whether trade union managers existed and, if so, what their roles were appeared to offer the prospect of examining a new area of trade union life. This research is based on interviews with 56 senior trade union staff in four trade unions formed by merger – CWU, PCS, UNiFI and UNISON. Only one of those individuals professed not to accept a managerial role and that person accepted that he had a responsibility to ensure that the union was managed. Original findings include the following:- • There is a category of employee in trade unions known as a ‘trade union manager’, a role not previously identified by empirical research and discussed in the literature. • Trade union management develops depending on the level of institutional support. In the case study unions, there were links between this and the stage of merger that the unions had reached. Prior to institutional acceptance, there are managers who do their best to manage, operating in something of a cocoon. • Trade union managers espouse trade union principles which include the notion of fairness, imputing a concern for the way people are treated, including the staff for whom they are responsible. • Management remains in many ways a problematic concept in trade unions, leading often to its undervaluation. Trade union managers may perceive that it involves the exercise of power of the powerless, judgment on the weak. Trade union managers may as a result be ambivalent at being judgmental and, consequently, at managing conduct or performance. • Trade union managers manage stakeholders in polyarchal organisations but boundaries with lay activists are unclear; they engage in contests to define those boundaries and to manage what they regard as their own responsibilities. • Boundaries may include those relating to conflictual relations, constitutional boundaries, moveable boundaries, staff boundaries and policy/political boundaries.
Keywords: Trade Union managers; Governance; Case study